THE EFFECT OF INTERPERSONAL COMMUNICATION AND WORK MOTIVATION ON JOB SATISFACTION OF CONTRACT EMPLOYEES AT PT. PERKEBUNAN NUSANTARA IV REGIONAL OFFICE II MEDAN - Muhammad Daffa Ramadhan Siregar; Iskandarini; Vivi Gusrini Rahmadani (CV. RADJA PUBLIKA, 2025)
This study aims to analyze the effect of interpersonal communication and work motivation on job satisfaction of contract employees (PKWT) at PT. Perkebunan Nusantara IV Regional Office II. The plantation sector, especially palm oil, has an important role in the Indonesian economy, but the work contract system is often associated with low levels of job satisfaction. Lack of interpersonal communication and work motivation are thought to be the main factors affecting job satisfaction of contract employees. This study uses a quantitative approach with the causal associative method. Data were collected through questionnaires distributed to 61 contract employees and analyzed using multiple linear regression. The classical assumption test was also conducted to ensure the validity of the research model. The results showed that interpersonal communication had a positive and significant effect on job satisfaction. The better the communication between employees and superiors, the higher the job satisfaction felt. Work motivation also had a positive and significant effect on job satisfaction, where employees with high motivation tended to be more satisfied with their jobs. Simultaneously, interpersonal communication and work motivation had a significant effect on job satisfaction of contract employees. These findings emphasize the importance of improving communication between employees and superiors as well as providing incentives and career development opportunities to increase work motivation to improve employee job satisfaction.